Radauti Municipal (Co)housing - Grosu, Gabriel Andrei (Vysoké učení technické v Brně. Fakulta architektury)
Since the beginning of the Ukrainian invasion, the booming demand for accommodation within proximity to the border turned into a delicate housing crisis. This project investigates the current housing condition made available for the Ukrainian refugees while searching for the best way of addressing the sudden increase in the medium and long-term housing demand. The findings of the investigation along with the input from many consultations with Ukrainian war refugees were translated into developing a detailed architectural design for a municipal (CO)housing refugee camp in the city of Radauti.

Since the beginning of the Ukrainian invasion, the booming demand for accommodation within proximity to the border turned into a delicate housing crisis. This project investigates the current housing condition made available for the Ukrainian refugees while searching for the best way of addressing the sudden increase in the medium and long-term housing demand. The findings of the investigation along with the input from many consultations with Ukrainian war refugees were translated into developing a detailed architectural design for a municipal (CO)housing refugee camp in the city of Radauti.
Radauti Municipal (Co)housing
Keywords: Ukraine; Invasion; War; Refugee; Housing Crisis; Urban Regeneration; (CO)Housing; Refugee Camp; Urban Regeneration; Radauti; Romania; Ukraine; Invasion; War; Refugee; Housing Crisis; Urban Regeneration; (CO)Housing; Refugee Camp; Urban Regeneration; Radauti; Romania